1993
DOI: 10.1152/jappl.1993.74.2.859
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic drainage of hypertonic solution from peritoneal cavity of anesthetized and conscious sheep

Abstract: Lymphatic drainage of the peritoneal cavity may reduce ultrafiltration in continuous ambulatory peritoneal dialysis. We assessed lymphatic drainage of the peritoneal cavity in sheep under dialysis conditions by cannulation of the relevant lymphatic vessels and compared lymphatic drainage in anesthetized and conscious animals. Lymph was collected from the caudal mediastinal lymph node and the thoracic duct, both of which are involved in the lymphatic drainage of the ovine peritoneal cavity. Volumes of a hyperto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It has previously been reported that respiratory movement is reduced in anesthetized animals lying on their back (38,39). Other investigators have also previously found decreased lymphatic outflow from the peritoneum under anesthesia (40)(41)(42) and have speculated that abdominal muscle tone plays a large role in driving flow out of the peritoneum. This concept is in agreement with our findings, although more research is necessary to elucidate the major driving forces for lymphatic flow from this serous cavity.…”
Section: Discussionmentioning
confidence: 89%
“…It has previously been reported that respiratory movement is reduced in anesthetized animals lying on their back (38,39). Other investigators have also previously found decreased lymphatic outflow from the peritoneum under anesthesia (40)(41)(42) and have speculated that abdominal muscle tone plays a large role in driving flow out of the peritoneum. This concept is in agreement with our findings, although more research is necessary to elucidate the major driving forces for lymphatic flow from this serous cavity.…”
Section: Discussionmentioning
confidence: 89%
“…In large an imals like sheep, lymph How rates have been measured by cannulation [5,11]. Unfortu nately, each small lymphatic vessel that drains the peritoneal cavity cannot be cannulated, so instead, investigators cannulate larger vessels further downstream from the peritoneal cavity.…”
Section: Direct Methodsmentioning
confidence: 99%
“…macromolecular tracers (by monitoring the mass of i.p. tracer that en ters a given lymph compartment and dividing by the concentration of the tracer in the peri toneal cavity) [11], One drawback with this technique is that the cannulation process may affect the flow rate [ 12], Moreover, since can nulation is not ethically feasible in humans, use of this technique to estimate lymph flow during PD requires extrapolation from ani mal data.…”
Section: Direct Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that the thoracic duct plays a specific role in lymphatic drainage from the serosal cavity of quadrupeds (43)(44)(45). Therefore, anatomical differences in the thoracic duct and the duct tributaries may also affect the outcomes of lymphogenous metastases.…”
Section: Serosal Membranes Lymphatic Stomata and Coelomic Fluid Draimentioning
confidence: 99%